(untitled) (Archives of Mechanics - Test, 2008)
The paper discusses finite volume WENO reconstruction applied to simulation of compressible 3D Euler flows. The main objective of this work is presentation of the new reconstruction procedure (third-order of accuracy in space), together with the procedure for integration of numerical fluxes applied to simulations of compressible 3D Euler flows, using unstructured meshes.